A systematic review on COVID-19 pandemic with special emphasis on curative potentials of Nigeria based medicinal plants - Johnson O. Oladele; Ebenezer I. Ajayi; Oyedotun M. Oyeleke; Oluwaseun T. Oladele; Boyede D. Olowookere; Boluwaji M. Adeniyi; Olu I. Oyewole; Adenike T. Oladiji (Heliyon, 2020)
Despite the frightening mortality rate associated with COVID-19, there is no known approved drug to effectively combat the pandemic. COVID-19 clinical manifestations include fever, fatigue, cough, shortness of breath, and other complications. At present, there is no known effective treatment or vaccine that can mitigate/inhibit SARS-CoV-2. Available clinical intervention for COVID-19 is only palliative and limited to support. Thus, there is an exigent need for effective and non-invasive treatment. This article evaluates the possible mechanism of actions of SARS-CoV-2 and present Nigeria based medicinal plants which have pharmacological and biological activities that can mitigate the hallmarks of the pathogenesis of COVID-19. SARS-CoV-2 mode of actions includes hyper-inflammation characterized by a severe and fatal hyper-cytokinaemia with multi-organ failure; immunosuppression; reduction of angiotensin-converting enzyme 2 (ACE2) to enhance pulmonary vascular permeability causing damage to the alveoli; and further activated by open reading frame (ORF)3a, ORF3b, and ORF7a via c-Jun N- terminal kinase (JNK) pathway which induces lung damage. These mechanisms of action of SARS-CoV-2 can be mitigated by a combination therapy of medicinal herbs based on their pharmacological activities. Since the clinical manifestations of COVID-19 are multifactorial with co-morbidities, we strongly recommend the use of combined therapy such that two or more herbs with specific therapeutic actions are administered to combat the mediators of the disease.